2016
DOI: 10.1080/14740338.2016.1225720
|View full text |Cite
|
Sign up to set email alerts
|

No substantial gender differences in suspected adverse reactions to ACE inhibitors and ARBs: results from spontaneous reporting system in Campania Region

Abstract: This analysis suggested no substantial gender differences. Further studies such as randomized population studies or meta-analysis of ACE inhibitors and ARBs randomized studies are needed to clarify whether gender differences exist in the safety profile of these drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
9
1
Order By: Relevance
“…In the Italian study, the fact that ACE-Is and ARBs were prescribed to a greater extent in men during the study period was discussed [14], and the lack of adjustment to prescription data may explain why their results differ from ours. The results from our study are in line with the literature referring to pharmacokinetic and pharmacodynamic differences, giving relatively higher exposure in women to a given dose [3].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In the Italian study, the fact that ACE-Is and ARBs were prescribed to a greater extent in men during the study period was discussed [14], and the lack of adjustment to prescription data may explain why their results differ from ours. The results from our study are in line with the literature referring to pharmacokinetic and pharmacodynamic differences, giving relatively higher exposure in women to a given dose [3].…”
Section: Discussionmentioning
confidence: 80%
“…However, in a regional pharmacovigilance center in France, there was no sex difference in the incidence of reporting of ADRs overall [ 13 ]. Furthermore, no sex difference was seen in suspected ADRs to ACE inhibitors and ARBs in spontaneous reports in the Campania region, Italy [ 14 ]. Spontaneous reporting of ADEs is an important tool in obtaining better knowledge about sex differences in ADEs, in addition to the information from the clinical trials conducted before the drug has been introduced on the market.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst men have an increased risk of gout and hyperuricemia and, therefore, are more prone to be treated with allopurinol, we found that ADRs, especially serious cutaneous ADRs, were more common in women. This is not surprising because females seem to be more likely at risk to experience ADRs due to sex-specific differences in the pharmacokinetics and pharmacodynamics of drugs [34][35][36][37]. Furthermore, literature data confirm that both SJS and TEN could occur at any age, but appear to be more prevalent in adults, with a slight predominance in women [38,39].…”
Section: Overall Resultsmentioning
confidence: 94%
“…Our study represents one of the activities performed in Campania Region in the field of pharmacovigilance (Rafaniello et al, 2016a ; Sessa et al, 2016a , b ; Sportiello et al, 2016a , b ) with the aim to better define the safety profile of drugs and to improve their safe use in routine clinical practice. The results of our study demonstrated that biotech drugs used in several clinical settings in Campania Region showed overall good tolerability profiles.…”
Section: Discussionmentioning
confidence: 99%